‘Slavery and technology in pre-industrial contexts’ - Tracey Rihll (Slave Systems: Ancient and Modern, 2008)
This paper develops a general model of slavery and technology in ancient Greece and Rome. Seven parameters are identified: the skill or care level of the work being performed; the motivation provided to the workers; the technical education of the workers; the material or cash capital investment required by an innovation; the physical and socio-economic benefits of an innovation; the physical and socio-economic risks of an innovation; the physical mobility of skilled workers and transaction costs. As a result of the analysis I argue that slavery was not antithetical to technical progress when the slaves were motivated by reward, especially manumission. I also argue that there was a great deal of technological progress in classical antiquity, and that slavery, which forced people with diverse technical skills and education across linguistic and cultural boundaries, was the main agent of technology transfer and innovation in the ancient world.